Health literacy and self-management among middle-aged and young hypertensive patients: a parallel mediation effect of illness perception and self-efficacy - Liu, Yaqing; Jiang, Feng; Zhang, Meicheng; Niu, Haoran; Cao, Jianbo; Du, Sixian; Chen, Hongfeng; Wang, Hui; Gong, Liwen; Rao, Feifei; Wu, Huan (Frontiers in Psychology, 2024)
Background: Hypertension is increasingly prevalent among young and middle-aged populations in rural China, accompanied by suboptimal self-management. Given that this population forms the backbone of the labor force, enhancing their self-management capabilities is crucial for improving overall population health. Studies indicate that individuals with good health literacy are more likely to effectively manage their health. Methods: Grounded in the health literacy skills framework, a model was constructed in this study to examine the impact of health literacy on self-management among young and middle-aged hypertensive patients in rural China. Meanwhile, the mediating roles of illness perception and self-efficacy were also verified. Using a multi-stage stratified random sampling method, 338 patients were recruited to participate in the study. Structural equation modeling was utilized to establish the relationship model, and bootstrap tests were carried out to examine the mediating effects. Results: The average self-management score was 70.45±11.36. Health literacy exhibited a positive correlation with self-management (standardized β=0.372, P<0.001). The mediating effects through illness perception and self-efficacy were 0.040 and 0.236, constituting 6.68% and 39.31% of the total effect, respectively. Conclusion: Illness perception and self-efficacy serve as parallel mediators amid the association between health literacy and self-management. Implementing psychological counseling and health education is imperative for augmenting selfmanagement competence and cultivating an adaptive coping mentality.